Analisis Kualitas FAME Menggunakan Metode Seven Tools dan FMEA Pada Departemen Laboratorium (Studi Kasus: PT. XYZ) - Sayyid Atho' Muzakki; Said Salim Dahda (Fakultas Teknik, 2023)
PT. XYZ is an industry that processes palm oil into oil to manufacture Fatty Acid Methyl Ester. Fatty Acid Methyl Ester (FAME) or commonly known as Biodiesel. This study aims to identify and analyze the factors that cause FAME products not to comply with standard specifications which can then be given proposals for improvement and resolution related to product quality defects. The incidence of defects that exceed the quality specification limit for FAME in moisture content parameters is 30.83%, soap content 3.33%, total glycerol 5% for 1 month. The solution method used uses seven tools and FMEA. With the use of the seven tools method, it is known that defective quality parameters are still within reasonable thresholds, and some of the factors that influence them are people, machines, methods, and raw materials. From the FMEA method, it is known that the material that must be repaired first with a value of RPN 320.